2017
DOI: 10.5902/2179460x26978
|View full text |Cite
|
Sign up to set email alerts
|

Mapeamento Da Fragilidade Ambiental Na Bacia Hidrográfica Do Reservatório Da Uhe Caçu - Goiás

Abstract: Resumo Abstract The fragility of the environment can be seen as a research proposal, whose basic principle is to define the different levels of fragility of natural environments and environments already altered by anthropic activities. This study aimed to evaluate the Environmental Fragility levels in the hydrographic basin of the Hydroelectric Plant reservoir in Caçu (UHE), in two distinct periods: before the formation of the reservoir (2009) and after the formation of the reservoir (2014). The methodology us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 3 publications
1
1
0
2
Order By: Relevance
“…approximately 50% of its area is covered by Entisol, whose erosion resistance class is considered very low, and when associated with annual crops, presents high potentiality to erosive processes. Similar fact is described by Braga et al 2017, in which the areas that were classified as high potential fragility are located in this type of soil. Galdino et al 2004 applied the Universal Soil Loss Equation and they found similar values (555.6 t.ha -1 .year -1 ) to these of the Cachoeira Cinco Veados Watershed, in the Alto Taquari watershed.…”
Section: Discussionsupporting
confidence: 83%
“…approximately 50% of its area is covered by Entisol, whose erosion resistance class is considered very low, and when associated with annual crops, presents high potentiality to erosive processes. Similar fact is described by Braga et al 2017, in which the areas that were classified as high potential fragility are located in this type of soil. Galdino et al 2004 applied the Universal Soil Loss Equation and they found similar values (555.6 t.ha -1 .year -1 ) to these of the Cachoeira Cinco Veados Watershed, in the Alto Taquari watershed.…”
Section: Discussionsupporting
confidence: 83%
“…Através dos estudos de Amaral e Ross (2009) observa-se que as modificações da cobertura do solo causadas pelas atividades agropecuárias degradam significativamente a terra, uma vez que essas práticas culminam para a exposição da superfície. Com isso, a exposição e consequentemente a compactação diminuem o grau de proteção do meio, uma vez que a ausência de vegetação faz com que ocorra o escoamento superficial, erosões, formações de voçorocas, dentre outras situações que tornam as áreas mais fragilizadas e instáveis (Braga et al, 2017).…”
Section: Fragilidade Ambiental Temporalunclassified
“…Thus, applying environmental fragility in studies evaluating watershed can guide policy decisions on monitoring and management regarding soil use planning, improving water quality for public supply. (Braga et al 2017; Abrão and Bacani 2018).…”
Section: Introductionmentioning
confidence: 99%